Visualisasi SD N 47 Kota Bengkulu Berbasis 3D Dengan Menggunakan Teknik Chrome Key Dan Sketchup - Ade Saputra; Dandi Sunardi; Ardi Wijaya; Agung Kharismah Hidayah (Jurnal Media Infotama, 2023)
Profile video is an electronic medium to convey information that is very effective in introducing a school. Through this visual media, all information can be easily digested by all circles of society. State Elementary School 47 Bengkulu City, Mem needs promotional media to the community to increase the admission of new students. Based on this, then to do the promotion, a profile video of Sekolah Dasar Negeri 47 bengkulu city was made. In making this video, Sketchup software and enscape are used to make it easier to create profile videos. The purpose of the research is to make a 3D animated video as a promotional medium at Sekolah Dasar Negeri 47 Bengkulu City. Research methods through multimedia system development models using Luther Sutopo's Multimedia Development Life Cycle (MDLC). The research was carried out as a promotional medium through 3D animated videos using the sketchup application. The respondent's due diligence test received a response of 87.5%, which means that the video profile that was made is liked by the general public.